Surface Quality Forming under Parts Finishing and Strengthening Treatment with an Eccentric Hardener - M. A. Tamarkin; E. E. Tishchenko; O. C. A. Hashash (Advanced Engineering Research, 2023)
Introduction. The formation of the quality parameters of the surface layer and the operational properties of the parts occurs throughout all stages of their manufacture. However, the decisive impact is most often exerted by the stages of finishing. Therefore, in modern digital engineering, the task of process support of high quality of the surface layer of the part is one of the challenges in solving the problem of improving the quality and reliability and increasing the life cycle of manufactured machines. Surface plastic deformation treatment is instrumental in improving the performance characteristics of machine parts. Its essence is that the required quality parameters of parts are obtained not by removing a layer of material, but by plastic deformation. During the processing, both the dimensions of the parts and the physical and mechanical properties of the surface layers are changed. In this case, the technologist has the opportunity to significantly increase the life cycle of the manufactured products through controlling the process. These studies are aimed at providing the required quality parameters of the surface layer under processing with an eccentric hardener.Materials and Methods. The article presents the results of research on a new method of surface plastic deformation treatment – with an oscillating eccentric hardener. The considered processing method enables to obtain high quality of the treated surface, to process large-sized parts in places that are stress concentrators, to process welds, small areas of surfaces, whose hardening is needed for the part to fulfill its intended service. A set of theoretical studies was carried out; their results provided determining the parameters of a single interaction of the indenter and the surface of the part, the diameter of the plastic imprint and its depth.Results. Dependences for determining the surface roughness, the depth of the hardened layer and the degree of deformation were obtained. The resulting formulas were tested for adequacy by experimental studies.Discussion and Conclusion. The obtained research results can be used in the technological design of surface plastic deformation treatment processes. Further tasks for the study of the considered processing method are determined.